Bem-estar de bovinos leiteiros em região tropical subúmida. - Santos, Severino Guilherme Caetano Gonçalves dos (2018)
The welfare of dairy cows is a major concern of the production system because of its impact on health and productivity as well as on public health. The objective of this study was to identify the main problems related to welfare in dairy herds managed in pasture in the Brejo Paraibano microregion of Brazil. For this, a transversal study was conducted in twelve (n = 12) dairy farms in the municipalities of Areia, Alagoa Grande, Serraria and Pilões, PB, Brazil. Each farm was visited only once, during the visit the number of cows from the herd, type and number of milking per day, daily milk production and time of access to pasture were recorded. Body condition score, hygiene score, body injuries and qualitative behavior assessment (QBA) were measured based on the animal. A total of 335 dairy cows were evaluated; the herds ranged from 14 to 43 lactating cows, as an average yield of 8.4 ± 3.25 L / cow / day. Of the evaluated herds, 26% of the cows presented low body condition, 82% with corporal injuries and 20% with dirty legs. In the qualitative evaluation of the behavior, a principal component analysis provided two CPs; CP1 presented high correlation with positive body expressions (e.g., active, sociable, excited, positively occupied) and CP2 was associated with negative terms of body expression (e.g., apathetic, frustrated, restless). In addition, the condition of the integument of five body regions (neck / palette / dorsum, carpal or knee, flank / side / udder, tarsus or hindquarters) of each cow was evaluated and scored (0 = does not occur; ) for blemishes, lesions and bumps. Of the 335 dairy cows observed, 267 (81.5%) presented injuries in some body region. The highest prevalence of hairless spots occurred in the hock region (65.4 ± 5.03%), lesions in the flank / side / udder region (34.5 ± 1.46%) and swellings in the neck / palate region / back (52.9 ± 5.86%). In conclusion, the evaluation of the indicators of body scoring, body injury and body parts observed showed the importance of promoting improvements in the conditions of grazing, management and facilities, in order to enable better health and animal welfare performance.